Appropriateness in prescribing PPIs: A position paper of the Italian Society of Gastroenterology (SIGE) — Study section "Digestive Diseases in Primary Care". Issue 9 (September 2018) - Savarino, Vincenzo; Tosetti, Cesare; Benedetto, Edoardo; Compare, Debora; Nardone, Gerardo
Abstract: The introduction of proton pump inhibitors (PPIs) into clinical practice about thirty years ago has greatly improved our therapeutic approach to acid-related diseases for their well-recognized efficacy and safety. Despite the well-defined indications, however, the use of PPIs continues to grow every year in both western and eastern countries and this phenomenon poses serious queries that include the onset of potential adverse effects and the increase in health care costs. The major reason explaining this worrying market expansion is the inappropriate use of PPIs. In order to re-establish a correct use of these effective drugs in daily clinical practice, the Italian Society of Gastroenterology (SIGE), nominated a panel of experts who reviewed the available clinical literature and produced a series of updated position statements on the use of PPIs in clinical practice.